In vivo assessment of interictal sarcolemmal membrane properties in hypokalaemic and hyperkalaemic periodic paralysis. Issue 4 (April 2020) - Tan, S. Veronica; Suetterlin, Karen; Männikkö, Roope; Matthews, Emma; Hanna, Michael G.; Bostock, Hugh
Highlights: The muscle resting membrane potential is depolarised in HypoPP, but mostly normal in HyperPP. Muscle excitability studies support the presence of a window current in HyperPP. Excitability measures distinguish between HypoPP and HyperPP, and HyperPP and paramyotonia congenita. Abstract: Objective: Hypokalaemic periodic paralysis (HypoPP) is caused by mutations of Cav 1.1, and Nav 1.4 which result in an aberrant gating pore current. Hyperkalaemic periodic paralysis (HyperPP) is due to a gain-of-function mutation of the main alpha pore of Nav 1.4. This study used muscle velocity recovery cycles (MVRCs) to investigate changes in interictal muscle membrane properties in vivo . Methods: MVRCs and responses to trains of stimuli were recorded in tibialis anterior and compared in patients with HyperPP( n  = 7), HypoPP ( n  = 10), and normal controls ( n  = 26). Results: Muscle relative refractory period was increased, and early supernormality reduced in HypoPP, consistent with depolarisation of the interictal resting membrane potential. In HyperPP the mean supernormality and residual supernormality to multiple conditioning stimuli were increased, consistent with increased inward sodium current and delayed repolarisation, predisposing to spontaneous myotonic discharges. Conclusions: The in vivo findings suggest the interictal resting membrane potential is depolarized in HypoPP, and mostly normal in HyperPP. The MVRC findings in HyperPP are consistent with presence of a window current, previously proposed on the basis of in vitro expression studies. Although clinically similar, HyperPP was electrophysiologically distinct from paramyotonia congenita. Significance: MVRCs provide important in vivo data that complements expression studies of ion channel mutations.